Research on the Use of Renewable Energy in the Automation of Electric Generators - Abatbayevich, Dauletov Kalniyaz; qizi, Kulmuratova Aliya Janabay (Research Parks Publishing LLC, 2023)
Currently, in order to meet the rapidly growing energy needs in the Republic of Uzbekistan, it is necessary to use all energy sources. Regenerable the energy is unlimited and efficient, and it gives us the results we expect. However, its main disadvantage is in renewable energy sources. To solve this problem of control and management of a hybrid renewable energy system, it will consist of multiplying renewable electricity sources built by combining several separate energy sources. Energy economy, reliability and due to their flexibility, these hybrid systems will be able to exceed the limits of individual energy production technologies. Republic of Uzbekistan In 2021-2023, it created several incentives for the use of renewable electricity. This means the use of solar energy, that is, the program of obtaining energy with the help of solar panels and self-sufficiency in electricity. Optimal solar panel sizing, control, and power management strategies are discussed in detail to exploit its potential. Electricity Several research studies have been conducted on the implementation of measurement, control, power management and optimization processes. The article presents a critical analysis and shortcomings and control of existing electricity systems in the selection of optimization parameters and several processes for designing power control schemes are reviewed. Furthermore, the study was able to highlight various challenges/barriers. Wind and Solar energy highlight the possible future possibilities and the results of studies on increasing the power of the electrical system in the field of control, power management, optimization and optimal measurements were studied.